Hypertension and reduced bone mineral density: unexpected pathogenetic mechanisms - A. F. Sheptulina; Yu. A. Golubeva; A. A. Yafarova; T. T. Tsoriev; A. R. Kiselev; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2024)
Hypertension (HTN) and osteoporosis are major age-related conditions, each of which causes significant morbidity and mortality. To date, data have been accumulated on the relationship between hypertension, markers of bone matrix formation and bone resorption. This review article discusses the relationship between hypertension and reduced bone mineral density, as well as previously unknown pathogenetic mechanisms underlying it.